IMPROVING STUDENTS’ ENGLISH SKILLS BY WATCHING MINING VIDEOS - Indri Lesta Siwidiani (UPN Veteran Yogyakarta, 2022)
Nothing is impossible in this world, this expression shows that when people want to achieve their dreams, they must try hard to make them come true, there’s a saying: no pain no gain. Anyone needs effort to push themselves to be such persons they want. For mining engineering students who want to continue their studies abroad, to become article writers in international media, to become international speakers or presenters at international seminars or workshops or at events, but English proficiency is their barriers. The recommended way to improve their English skills is by watching mining videos habitually, regularly and consistently at any time they have spare time. They will not only be fluent in mastering English both in written and spoken forms, but they will also gain a lot of experience, knowledge and technology applied in mining engineering and in ores or mineral processing more broadly and globally.